VISTA-mediated immune evasion in cancer - Raymond J. Zhang; Tae Kon Kim (Experimental and Molecular Medicine)
Abstract Over the past decade, V-domain immunoglobulin suppressor of T-cell activation (VISTA) has been established as a negative immune checkpoint molecule. Since the role of VISTA in inhibiting T-cell activation was described, studies have demonstrated other diverse regulatory functions in multiple immune cell populations. Furthermore, its relevance has been identified in human cancers. The role of VISTA in cancer immune evasion has been determined, but its mechanisms in the tumor microenvironment remain to be further elucidated. Understanding its contributions to cancer initiation, progression, and resistance to current treatments will be critical to its utility as a target for novel immunotherapies. Here, we summarize the current understanding of VISTA biology in cancer.